1996
DOI: 10.1038/ng0796-366
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial detachment due to absence of hemidesmosomes in integrin β4 null mice

Abstract: Integrins are heterodimeric transmembrane glycoproteins which are engaged in a variety of cellular functions, such as adhesion, migration and differentiation1. The integrin alpha 6 beta 4 is expressed on squamous epithelia, on subsets of endothelial cells, immature thymocytes and on Schwann cells and fibroblasts in the peripheral nervous system. In stratified epithelia, alpha 6 beta 4 is concentrated in specialised adhesion structures, called hemidesmosomes, which are implicated in the stable attachment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
252
1
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(267 citation statements)
references
References 32 publications
10
252
1
4
Order By: Relevance
“…A reduction of integrin ␤4 expression also has been reported in mice deficient in integrin ␣6, another binding partner of integrin ␤4 (Georges- Labouesse et al 1996), whereas in integrin ␤4 (−/−) mice van der Neut et al 1996) a reduction in the expression of HD1 was noticed (van der Neut et al 1996). In addition, a recent report suggested that the subcellular distribution of HD1 is determined by the cytoplasmic domain of the ␤4 subunit (Sanchez-Aparicio et al 1997), arguing in favor of a direct interaction between plectin and integrin ␤4 within the hemidesmosomal complex.…”
Section: Plectin a Stabilizer Of Hemidesmosomes And Other Junctionalmentioning
confidence: 91%
“…A reduction of integrin ␤4 expression also has been reported in mice deficient in integrin ␣6, another binding partner of integrin ␤4 (Georges- Labouesse et al 1996), whereas in integrin ␤4 (−/−) mice van der Neut et al 1996) a reduction in the expression of HD1 was noticed (van der Neut et al 1996). In addition, a recent report suggested that the subcellular distribution of HD1 is determined by the cytoplasmic domain of the ␤4 subunit (Sanchez-Aparicio et al 1997), arguing in favor of a direct interaction between plectin and integrin ␤4 within the hemidesmosomal complex.…”
Section: Plectin a Stabilizer Of Hemidesmosomes And Other Junctionalmentioning
confidence: 91%
“…The a6f34 integrin plays an important role in the assembly of hemidesmosomes (Vidal et al 1995;Dowling et al, 1996;Georges-Labouesse et al, 1996;Niessen et al, 1996;Van der Neut et al, 1996), and its association with HD1 may provide a link between the keratin filaments and the plasma membrane during early hemidesmosome formation. This role of HD1 /plectin is supported by the observation that in patients deficient for plectin/HD1 no keratin filaments are attached to hemidesmosomes (Gache et al, 1996;McLean et al, 1996;Smith et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted inactivation of hemidesmosome components in mouse shows that laminin-332 and a6b4-integrin are critical to construct stable hemidesmosomes (Table 2A) (Georges-Labouesse et al, 1996;van der Neut et al, 1996;Ryan et al, 1999;Meng et al, 2003). Their absence leads to severe skin blistering and near absence of hemidesmosomes, although reduced amounts of BP230, BP180, and plectin can still associate with the basal membrane.…”
Section: Initial Hemidesmosome Assemblymentioning
confidence: 99%